Understanding Knowledgeable Workers’ Behavior Toward COVID-19 Information Sharing Through WhatsApp in Pakistan - Islam, Talat; Mahmood, Khalid; Sadiq, Misbah; Usman, Bushra; Yousaf, Sheikh Usman (Frontiers in Psychology, 2020)
Using social media through mobile has become a major source of disseminating information, however, what are the motivations that impact social media users’ intention and actual information sharing behavior need further examination. To this backdrop, drawing on theory of uses and gratification, theory of prosocial behavior, and theory of planned behavior we aim to examine various motivations towards information sharing behaviors in a specific context (COVID-19). We collected data from 388 knowledgeable workers through google form and applied structural equation modeling to test hypotheses. We noted that individuals behave seriously towards crisis-related information as they do not share COVID-19 information on WhatsApp to be entertained, seeking status or information, but to help others. Further, we noted norms of reciprocation, habitual diversion, and socialization as motivators that augment WhatsApp users’ positive attitude towards COVID-19 information sharing behavior.